HPMC- A Marvel Polymer for Pharmaceutical Industry-Patent Review - Guarve, Kumar; Kriplani, Priyanka (Recent Advances in Drug Delivery and Formulation, 2021)
At the present time, designing of defined release dosage forms, either controlled, sustained, modified, are gaining much importance. For the development of such delivery systems, proper blend of polymers is required so that drug release occurs by polymer erosion, swelling, diffusion/ dissolution. HPMC (Hydroxypropyl Methylcellulose) is the most commonly used cellulosic polymer available in various grades to develop such types of systems. Depending upon the molecular weight and viscosity chosen, it can be applied for emulsification, adhesion, bonding, thickening, suspension, film forming and gelation. It consists of polymeric units linked together, which retain water, thereby acting as an excellent hydrophilic gel forming polymer. It generally hydrates on the outer surface to form a gelatinous layer. It swells, expands upon contact with water and releases the drug in predetermined manner initially and then forms viscous gel to control the release further. The objective of the present review is to overview the recent patents and articles of HPMC, its properties, grades and its use in various drug delivery systems and as a binder, dispersing agent, bioavailability enhancer and as capsule forming material have been identified and reviewed.
Keywords: hydrophilic polymer